Biomass derived beta-cyclodextrin-SO3H as a solid acid catalyst for esterification of carboxylic acids with alcohols - Thombal, Raju S.; Jadhav, Amol R.; Jadhav, Vrushali H. (RSC Advances, 2015)
A novel beta-cyclodextrin-SO3H carbon based solid acid catalyst was prepared in a convenient and ecofriendly manner and was characterized using FTIR, PXRD, EDAX and NH3TPD to illustrate that the carbon material has been functionalized with -SO3H, -COOH and -OH groups. The catalyst was studied for esterification of various carboxylic acids and alcohols under solvent free conditions and showed excellent catalytic performance and gave good yields of esters in the range 78-99% at 70 degrees C. No solvent was used either for catalyst preparation nor for esterification reaction. The catalyst can be easily recovered by simple filtration and reused for subsequent three runs without any significant impact on yields of products. The main advantage of this methodology is easy and ecofriendly catalyst preparation, easy catalyst separation, practical simplicity, safe reaction conditions, recyclable catalyst and high product yields.